2007
DOI: 10.1016/j.arcmed.2006.10.013
|View full text |Cite
|
Sign up to set email alerts
|

APOC3 Promoter Polymorphisms C-482T and T-455C Are Associated with the Metabolic Syndrome

Abstract: These data, therefore, suggest that the APOC3 promoter polymorphisms C-482T and T-455C are associated with the MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 51 publications
8
56
1
2
Order By: Relevance
“…The between-study heterogeneity may have arisen for one of the following reasons. First, different diagnostic criteria for MetS: IDF (Csép et al, 2007;Turkovic et al, 2012), American Heart Association/National Heart, Lung, and Blood Institute (AHA/NHLBI) (Yamada et al, 2008;Oguri et al, 2009); and Adult Treatment Panel III guidelines (ATPIII) (Vimaleswaran et al, 2006;Miller et al, 2007). Second, ethnicity differences; the T allele frequencies of controlsubject Croatians, Indians, Romanians, Han Chinese, and Japanese were 0.224, 0.269, 0.281, 0.297, and 0.329, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The between-study heterogeneity may have arisen for one of the following reasons. First, different diagnostic criteria for MetS: IDF (Csép et al, 2007;Turkovic et al, 2012), American Heart Association/National Heart, Lung, and Blood Institute (AHA/NHLBI) (Yamada et al, 2008;Oguri et al, 2009); and Adult Treatment Panel III guidelines (ATPIII) (Vimaleswaran et al, 2006;Miller et al, 2007). Second, ethnicity differences; the T allele frequencies of controlsubject Croatians, Indians, Romanians, Han Chinese, and Japanese were 0.224, 0.269, 0.281, 0.297, and 0.329, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies showed a trend of elevated OR for the allele T (Vimaleswaran et al, 2006;Miller et al, 2007;Csép et al, 2007;Yamada et al, 2008;Oguri et al, 2009). Only one study showed a trend in the opposite direction (Turkovic et al, 2012).…”
Section: A B Cmentioning
confidence: 97%
“…4,9,40 Several groups reported about LPL and proteins involved in LPL activity, as apoCIII and apoAV in type III patients. 13 -16 In accordance with this hypothesis, we replicated in the largest type III cohort thus far, associations for polymorphisms in proteins involved in the lipolysis of lipoproteins: the 3238 G4C polymorphism in the APOC3 gene (in LD Lipolysis genes in type III hyperlipoproteinemia P Henneman et al with APOA5 À1131 T4C polymorphism) and the c.27 G4A mutation in the LPL gene.…”
Section: Genotype and Allele Frequenciesmentioning
confidence: 99%
“…Further, it acts as a constituent of triglyceride-rich lipoprotein particles, inhibiting their LPL-induced hydrolysis, and interferes with receptor-mediated lipoprotein uptake in liver (Yu et al, 2011). However, the -455T>C variant reduces the binding of transcription factors to its promoter elements, resulting in the dyslipidemia and abnormal glucose homeostasis associated with CHD risk (Miller et al, 2007). Interestingly, Yu et al (2011) failed to find an association between the APOC3 -455T>C SNP and increased CHD risk in a Han Chinese population, although promoter variants did have a significant impact on plasma TG and APOC3 levels.…”
Section: Discussionmentioning
confidence: 99%